Teaching Case Study : Sustaining the Lawande Super Store amidst growing Competition - Lawande, Radhika; Singhal, Divya (Journal of Contemporary Research in Management (JCRM), 2018)
To analyze the scope of sustaining a super market alongside new entrants and growing competition in the retail market.